Decreased serum levels of CTRP12/adipolin in patients with coronary artery disease in relation to inflammatory cytokines and insulin resistance. (January 2019) - Fadaei, Reza; Moradi, Nariman; Kazemi, Tooba; Chamani, Elham; Azdaki, Nahid; Moezibady, Sayed Ali; Shahmohamadnejad, Shiva; Fallah, Soudabeh
Highlights: Serum levels of CTRP12 were found to be lower in CAD patients. Serum levels of CTRP12 independently associated with risk of CAD. CTRP12 negatively associated with BMI, HOMA-IR, TNF-α and IL-6 in CAD patients. CTRP12 positively associated with adiponectin and HDL-C in CAD patients. Abstract: Coronary artery disease (CAD) is the leading cause of death worldwide. Atherosclerosis as the main underlying mechanism of CAD is associated with inflammation and adipose tissue dysfunction. C1q/TNF-related protein12 (CTRP12) is a newly discovered adipokine which is a paralog of adiponectin. CTRP12 has anti-inflammatory and insulin sensitizing effects. Circulating levels of this adipokine have been reported to be lower in patients with type 2 diabetes and women with polycystic ovarian syndrome. The present study was undertaken for the first time to evaluate serum levels of CTRP12 in CAD patients and its association with anthropometric and biochemical parameters. Serum levels of CTRP12 were measured using ELISA kit in 188 CAD patients (angiography confirmed) and 70 controls. The serum levels of adiponectin, TNF-α and IL-6 were measured using ELISA kits. Serum levels of CTRP12 were found to be lower in CAD patients (585.48 ± 201.67 pg/mL) than in the controls (814.86 ± 247.85 pg/mL; p < 0.001). CTRP12 also showed an independent association with the risk of CAD (OR [CI] = 0.998 [0.996–0.999]; p = 0.019). Moreover, it showed an inverse correlation with HOMA-IR (r = −0.298; p = 0.012) and TNF-α (r = −0.269; p = 0.023) and a positive correlation with adiponectin (r = 0.344; p = 0.003) in the controls. In CAD patients, CTRP12 was inversely correlated with BMI (r = −0.181, p = 0.013), HOMA-IR (r = -0.199; p = 0.006), TNF-α (r = -0.259; p < 0.001) and IL-6 (r = -320; p < 0.001) and a positive correlation with high density lipoprotein-cholesterol(r = 0.342; p < 0.001) and adiponectin (r = 0.398; p < 0.001). The present study showed for the first time that serum levels of CTRP12 are independently associated with CAD and that CTRP12 is associated with several CAD risk factors. The results suggest a possible link between CTRP12 and pathogenic mechanisms of atherosclerosis, such as inflammation and high density lipoprotein-cholesterol metabolism; however, more study is required in this regard.